“Den ensomme helt mod magtens og storpolitikkens skamfulde forsømmelser”: Den individuelle projektion af en nations kamp i FN-embedsmand Povl Bang-Jensens minde - Soós, Anita (Scandinavistica Vilnensis, 2023)
The Hungarian political and social discourse of the last decades often makes use of a national myth based on Hungarian history that focuses on a constant struggle for survival. The myth is built around the concept of the heroic Hungarians, who from time to time fight against a political and / or military preponderance. A narrative characteristic for the countries of East-Central and Eastern Europe has been created, which in its distinction between itself and the other concentrates on self-defence and victimhood, but at the same time emphasizes the nation’s superiority over the others. The image of the nation characterized by the uninterrupted struggle for survival becomes a schematic but effective tool in the political discourse. It is not a new narrative, but the actualization of the well-known, that finds appropriate events and personalities to disseminate the existing, traditional self-image. The paper attempts to demonstrate how the Danish United Nations official Povl Bang-Jensen and the role he played in the international politics after the Hungarian Revolution of 1956 has been used to convey this image. Based on memories, books and documentaries my goal is to discuss how individual recall of experienced events contributed to the (re)construction of Bang-Jensen’s personality. Furthermore, I try to shed light on how intertwining memories about a historical event, scientific research and history writing points to a changed perception of the scientific facts that are no longer considered objective and independent of human consciousness or actions. They describe a reality, which is influenced by consciousness and interpreted through textual formulations. The article argues that the subjective perspective constituted in the memories about Bang-Jensen creates an almost mythologized interpretation of the Danish diplomat as a symbol of freedom and morality, as well. The article was among others inspired by works of Maurice Halbwachs, Sabine Mollers, Annette Warrings and Bernard Eric Jensen on memory, historical awareness and the use of history.
Keywords: national stereotypes; national self-narrative; mythologizing; narrative of sacrifice; Povl Bang-Jensen